Fuzzy LMAW Method for Digital Marketing Technologies Assessment in Industry 4.0 age: Saudi Food Company Study Case - AOUADNI, Sourour; Aouadni, Ismahene (Journal of Ecohumanism, 2025)
Industry 4.0 is a new technological era which is revolutionizing business operations and customer interactions. Labor markets and policymakers entrusted with promoting pertinent skills and employment opportunities face significant challenges because of the rapidly changing technological landscape which is marked by automation and irreversible changes in the labor market. In this study, the Fuzzy Logarithm Methodology of Additive Weights (FLMAW) is used to evaluate Digital Marketing Technologies (DMT) in a real-world example from a Saudi food company. The new fuzzy MCDM model, which planners and decision-makers can use when assessing and selecting DMT in I4.0. Furthermore, a case study is carried out to illustrate the feasibility of the suggested approach. The results of the FTOPSIS and FCOPRAS approaches were compared with those of FLMAW to show which was more effective. In the second stage, the rank reversal problem was used to compare the sensitivity of the FLMAW method with the FTOPSIS method. As a result, the FLMAW method produces accurate outcomes.